1991
DOI: 10.1093/jac/27.suppl_c.73
|View full text |Cite
|
Sign up to set email alerts
|

Comparative kinetics and efficacy of amikacin administered once or twice daily in the treatment of systemic Gram-negative infections

Abstract: In an open randomized study the safety, efficacy and kinetics of a twice-daily amikacin (7.5 mg/kg bd) regimen (group A) was compared with a once-daily dosage (15 mg/kg) schedule (group B). Thirty patients were enrolled in each group. They were suffering from urinary tract infections (37), respiratory tract infections (17), soft-tissue infections (3), exacerbation of chronic prostatitis (1), acute cholangitis (1) and abdominal abscess (1). Aggravating factors were present in 77% and 60% of the groups respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 0 publications
0
22
1
Order By: Relevance
“…Regarding P. aeruginosa and Enterobacter cloacae, Garraffo et al demonstrated that the length of time for which amikacin levels were main- on May 12, 2018 by guest http://aac.asm.org/ tained above the MICs was an important parameter for bactericidal activity. In bronchial secretions from patients administered amikacin once daily, amikacin levels were above 8 mg/ liter for more than 12 h. Several clinical studies, some including critically ill patients, have shown that once-daily amikacin treatment can be as effective as the usual regimen (3,11,16). In a population of 45 patients with gram-negative bronchopneumonias, once-daily amikacin treatment could achieve a high clinical success rate, above 70%; moreover, Acinetobacter spp.…”
mentioning
confidence: 99%
“…Regarding P. aeruginosa and Enterobacter cloacae, Garraffo et al demonstrated that the length of time for which amikacin levels were main- on May 12, 2018 by guest http://aac.asm.org/ tained above the MICs was an important parameter for bactericidal activity. In bronchial secretions from patients administered amikacin once daily, amikacin levels were above 8 mg/ liter for more than 12 h. Several clinical studies, some including critically ill patients, have shown that once-daily amikacin treatment can be as effective as the usual regimen (3,11,16). In a population of 45 patients with gram-negative bronchopneumonias, once-daily amikacin treatment could achieve a high clinical success rate, above 70%; moreover, Acinetobacter spp.…”
mentioning
confidence: 99%
“…In addition, pharmacodynamic pa rameters such as concentration-dependent killing, inoculum-dependent killing, PAEs and PA SMEs have usually not been taken into consideration when dose and dose inter vals are determined for a new drug. The con centration-dependent killing and the long PAE of aminoglycosides have lately, however, led to a suggestion of once-daily dosage of these drugs instead of more frequently [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In patients treated with netilmicin, the once-daily regimen delayed the occurrence of nephrotoxicity in comparison with multiple daily dosing (ter Braak et al, 1990). Of the five studies dealing with more than 700 paediatric and adult patients, using the conventional regimen as control, less nephrotoxicity was observed with the once-daily dosing regimen in one study (P. E. Marik, personal communication), a second study supported the same trend (using phospholipiduria as the criterion; Tulkens, 1991), while the three other studies failed to indicate a significant difference (Giamarellou et al, 1991;Mailer et al, 1991;S. Lauwers, personal communication).…”
mentioning
confidence: 87%
“…These patients had various infectious conditions mainly caused by Gram-negative bacilli, and were most often treated with amikacin plus a /Mactam. One study favoured once daily dosing (Giamarellou et al, 1991), while the others indicated similar efficacy of the two regimens Tulkens, 1991;S. Lauwers, personal communication).…”
mentioning
confidence: 99%